Mid‐Latitude Spread‐F Structures Over the Geomagnetic Low‐Mid Latitude Transition Region: An Observational Evidence. Issue 5 (29th April 2020) - Sivakandan, M.; Mondal, S.; Sarkhel, S.; Chakrabarty, D.; Sunil Krishna, M. V.; Chaitanya, P. Pavan; Patra, A. K.; Choudhary, R. K.; Pant, T. K.; Upadhayaya, A. K.; Sori, Takuya
Abstract: An observational evidence of a unique plasma depletion event was captured by an O( 1 D) 630.0 nm airglow imager on 13 June 2018 over a transition region of geomagnetic low‐mid latitude, Hanle, Leh Ladakh, India (32.77°N, 78.97°E; Mlat. ~24.1°N). The observed plasma depletion structures are tilted at an angle of 13° ± 2° west of the geomagnetic north and drifted toward west. Collocated Global Navigation Satellite System‐Total Electron Content measurements confirm that the structures are indeed associated with TEC depletions. Simultaneous ionosonde measurements from Delhi, India (28.70°N, 77.10°E; Mlat. ~20.2°N) shows spread‐F signatures confirming that these structures are associated with the ionospheric irregularities. Interestingly, radar observations over the geomagnetic low‐latitude station Gadanki, India (13.5°N; 79.2°E; Mlat. ~6.5°N) reveal the absence of equatorial plasma bubbles on this night. Therefore, these observations strongly suggest that the observed structures in the airglow images over Hanle are associated with mid‐latitude spread‐F (MSF). These MSF structures are possibly affected by the shear in the zonal plasma drift that forces the field aligned plasma irregularity structures to tilt toward west. These observations, for the first time, bring out the presence of MSF structures over geomagnetic low‐mid latitude transition region. It is suggested that the plasma distribution over low latitudes plays an important role in the occurrence of MSF structures over this transition region. Understanding the source and characteristics of the plasma irregularity structures over this transition region can help in understanding the spatio‐temporal evolution of global L‐band scintillation in a better way. Plain Language Summary: Understanding the spatio‐temporal distribution of the ionospheric plasma irregularities is important in the operational forecasting of L‐band scintillation and therefore has important ramifications in the satellite‐based communication and navigation systems. Traditionally, plasma irregularities in the low and mid‐latitudes had received focused attentions in the past with very less attention has been paid over the low to mid‐latitude transition region. The present investigation provides an attempt toward that direction and proposes a mechanism on the relationship between the plasma distribution over low latitudes and the occurrence of the mid‐latitude plasma irregularities over the geomagnetic low‐mid latitude transition region. Comprehensive investigations are further needed in the future to understand and characterize the ionospheric plasma irregularity structures over this region. Key Points: An imaging observational evidence of a unique plasma depletion event was recorded over a transition region of geomagnetic low‐mid latitude Simultaneous observations from Ionosonde, GNSS‐TEC, and HF radar confirm that the structure is mid‐latitude FAIs with a small westward tilt The wind in lower thermosphere operated collisional shear instability in mid latitude ionosphere and leads to the tilt in FAIs striation